The Role of the Service Office in Managing Zakat, Infaq, and Sadaqah Funds, at LAZISMU Jember - Bashori, Dhofir Catur; Wahyudi, Rofiul (At-Taqaddum, 2024)
This study aims to examine the management and role of the LAZISMU Service Office in increasing the raising of Zakat, Infaq, Waqf, and Sadaqah (ZISWAF) funds at LAZISMU Jember Region. This research is a field research, with data collection methods used through interviews, observation and documentation. The data obtained were analyzed using descriptive analysis methods to describe the results of the study. The position of the LAZISMU Service Office is the same as the Zakat Collection Unit (UPZ) which has an important role in managing ZISWAF funds. This LAZISMU Service Office is in direct contact with the Amil Zakat to the mustahiq. Currently the number of LAZISMU Service Offices formed by LAZISMU Jember Region is 11 (eleven) Service Offices spread across the Branch. Referring to Law Number 23 of 2011 concerning Management of Zakat Article 1 paragraph 9, the functions and duties of the LAZISMU Service Office are to collect, distribute and utilize zakat. However, in practice several LAZISMU Jember Service Offices have not run optimally in managing these zakat funds. The influencing factors are; First, the lack of human resources in the LAZISMU Service Office. Second, the lack of public awareness to pay zakat through Amil Zakat Institutions. Third, there is still a lack of knowledge of the Service Office administrators regarding the management of zakat. Fourth, the lack of guidance from LAZISMU Jember Region to the Service Office administrators. So that this greatly influences the role and contribution of the LAZISMU Service Office to the raising of ZISWAF funds at LAZISMU Jember Region. Suggestions given by this study is the need of intensive guidance for zakat managers in the Service Office by LAZISMU Jember Region. It is hoped that with the guidance for Service Office administrators they can improve their ability to manage and ZISWAF, so as to be able to optimize the potential of existing zakat, especially in Jember Regency